Pertumbuhan dan Kandungan Vitamin C Microgreen Bayam Merah (Amaranthus tricolor) pada Berbagai Konsentrasi Nutrisi dan Media Tanam - Sari, Komang Tri Astiti; Sesanti, Rizka Novi; Kartina, Raida; Sismanto, Sismanto (Journal of Horticulture Production Technology, 2024)
This study aims to evaluate the growth and vitamin C content of red amaranth microgreens (Amaranthus tricolor) under various nutrient concentrations and growing media. The experimental design used in this study was a Randomized Complete Block Design arranged factorially 5 x 3 (15 treatments) with 3 repetitions. The first factor was the concentration of hydroponic nutrients at levels of 0 ppm, 100 ppm, 200 ppm, 300 ppm, and 400 ppm. The second factor was the combination of growing media, namely sand + sawdust, sand + rice husk charcoal, and sand + cocopeat, with a 1:1 ratio for each combination. Data obtained from the observed variables were analyzed using variance analysis and further tested with an LSD test at a 5% significance level. The observed parameters included germination rate (%), plant height (cm), number of leaves, leaf color, root length (cm), number of roots, plant weight (mg), and vitamin C content. The results showed that the use of sand + rice husk charcoal as a growing medium was very suitable for the germination of red spinach microgreens. However, for leaf color and root length, the use of sand + cocopeat was better. The sand + cocopeat medium combined with nutrient concentrations of 300 ppm and 400 ppm produced the best plant height and sample weight compared to other treatments. Furthermore, the sand + sawdust medium was very effective in producing the number of roots and the vitamin C content of red spinach microgreens.